Physiology and Transcriptomics Analysis Reveal the Contribution of Lungs on High-Altitude Hypoxia Adaptation in Tibetan Sheep - Zhao, Pengfei; Zhao, Fangfang; Hu, Jiang; Wang, Jiqing; Liu, Xiu; Zhao, Zhidong; Xi, Qiming; Sun, Hongxian; Li, Shaobin; Luo, Yuzhu (Frontiers in Physiology, 2022)
The Tibetan sheep is an indigenous species on the Tibetan plateau with excellent adaptability to high altitude hypoxia and is distributed at altitudes of 2500m to 5000m. The high altitude hypoxia adaptation of Tibetan sheep requires adaptive reshaping of multiple tissues and organs, especially the lungs. To reveal the mechanisms of adaptation at the tissue and molecular levels in the lungs of Tibetan sheep under hypoxic conditions at different altitudes, we performed light and electron microscopic observations, transcriptome sequencing, and enzyme-linked immunosorbent assay studies on the lungs of Tibetan sheep from three altitudes (2500m, 3500m and 4500m). The results showed that in addition to continuous increase in pulmonary artery volume, thickness and elastic fiber content with altitude, Tibetan sheep increasing the hemoglobin (Hb) concentration at altitude of 3500m, while decreasing Hb concentration and increasing the surface area of gas exchange and capacity of the blood at altitude of 4500m. Other than that, some important differentially expressed genes related to angiogenesis (FNDC1, HPSE and E2F8), vasomotion and fibrogenesis (GJA4, FAP, COL1A1, COL1A2, COL3A1 and COL14A1), and gas transport (HBB, HBA1, APOLD1 and CHL1) were also identified, these discoveries at the molecular level explain to some extent the physiological findings. In conclusion, the lungs of Tibetan sheep adopt different strategies when adapting to the different altitudes, these findings are valuable to understanding the basis of survival of indigenous species on the Tibetan Plateau.